ТЕРМОАКТИВИРОВАННОЕ ВСПЕНИВАНИЕ ГИДРОТЕРМАЛЬНЫХ CA-NA-ЦЕОЛИТОВ - Казанцева Л.К.; Белицкий И.А.; Дементьев С.Н.; Паукштис Е.А.; Фурсенко Б.А. (My University, 2000)
Boiling of natural zeolites at high temperatures is the major peculiarity by which they are recognized and From which they derived their name. The micromechanism of this process was studied by IR spectroscopy. It has been established that the source of the gas phase in the process is not the initial "zeolite water", as supposed earlier, but the product of its high-temperature evolution, which passes through three stages: 1) dissociation of the "zeolite water" (released during partial dehydration of the zeolite) under the action of the electrostatic field of the coordinatively unsaturated polyvalent cations; 2) hydroxylation of the aluminosilicate framework; 3) dehydroxylation of the latter with release of gas H2O. This gas phase causes boiling of natural zeolites at high temperatures as they reach a pyroplastic stare. Small polyvalent cations, such as Ca2+, Mg2+ etc., play an important role in high-temperature hydroxylation of zeolites and, correspondingly, in their boiling, as they have a high charge density and, hence, a high polarization capacity.